Penerapan Media Sosial Dan Photoshoot Dalam Menunjang Ekonomi Pengrajin Batik Dan Patung Di Desa Bejijong - Dwi Prasetyo; Marselinus PRG; Esmeralda VL; Elsada RP; Kresna DWP; Galle E (LPPM Stikosa - AWS, 2021)
The introduction of social media and photoshoots to the community in Bejijong Village is an important thing to do to make Bejijong Village more aware of social media as a promotional medium and the people of Bejijong Village are able to improve the economy. This social media introduction and photoshoot program was well received by the community in Bejijong Village. Bejijong village is a village that is unique in that it has a house that resembles a Joglo shape like the Majapahit kingdom. This research involves the community around the Bejijong Village area such as people who trade to help advance their business by teaching Bejijong Village residents to be able and independent to use social media as a means of promoting trade in Bejijong Village residents in order to improve the economy. This study uses a descriptive qualitative method where the research data is in the form of primary data sources for the community in Bejijong Village. Data was collected by using interview, observation, and documentation techniques. The instrument used for this research is a human instrument, namely the researcher himself. To maintain the validity of the data, the data analysis stage is carried out starting from the data reduction stage, data presentation, and drawing conclusions. Based on the results of the research, the residents of Bejijong Village are still unable to maximize Instagram social media as a promotional media.